Efficacy of Four Entomopathogenic Fungi as Biopesticide Candidates against Bemisia tabaci on Soybean - Prayogo, Yusmani; Ginting, Sempurna; Bayu, Marida Santi Yudha Ika; Baliadi, Yuliantoro; Harnowo, Didik; Indiati, Sri Wahyuni; Susanto, Gatut Wahyu Anggoro; Suryadi, Yadi; Trizelia, Trizelia; Widiarta, I Nyoman; Mejaya, Made Jana; Fortus, Sernan Entierro; Peuo, Vibol (AGRIVITA Journal of Agricultural Science, 2026)
Bemisia tabaci is a major pest of soybeans and a vector of plant viruses. This study aimed to evaluate and compare the efficacy of four entomopathogenic fungi for suppressing B. tabaci populations on soybeans. The four treatments were L. lecanii, A. aleyrodis, M. anisopliae, and B. bassiana, a comparison with the insecticide thiamethoxam and a control group without treatment. The four types tested were able to suppress B. tabaci populations by up to 75%, with A. aleyrodis being especially effective. There was no significant difference in efficacy between the four types and the insecticide thiamethoxam. Validating the efficacy of entomopathogenic fungi, there were no significant differences in plant height, dry stover weight, or number of pods between treatments with the insecticide thiamethoxam. However, significant differences occurred in the number of empty pods and seed weight, reducing yield losses by up to 78%. There was a positive correlation between the B. tabaci population and the number of empty pods (r = 0.80), while there was a negative correlation between the B. tabaci population and plant height and soybean yield (r = -0.56 and r = -0.54, respectively).